(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
This article explores the phenomenon of English neologisms and borrowings in the Russian and Uzbek languages. It examines the linguistic, sociolinguistic, and cultural implications of the increasing presence of English elements in these languages. The study highlights the processes of semantic adaptation, grammatical integration, and hybridization that occur when English words are borrowed into Russian and Uzbek. It also discusses the influence of technology, popular culture, and language contact effects on the adoption of English borrowings. Additionally, the article addresses language attitudes, translation challenges, and the role of language planning and policy in managing the influx of English borrowings. Overall, the research provides insights into the dynamic nature of language evolution and the complex interplay between English and the Russian and Uzbek languages.